Letters from the American Red Cross to Max Bredig and Liselotte Zadek, 1942-1945 - Davis, Robert Courtney (1942)
Letters from the American Red Cross to Max Bredig (1902-1977) and Liselotte Zadek. The letters seem to come with correspondence through the American Red Cross. The letter contains recognition of a letter, censorship information, and instructions for sending a reply.
Keywords: Schnell, Eva, 1913-1944; Schnell, Alfred, 1900-1944; American Red Cross; Bredig, Max Albert, 1902-1977; Zadek, Liselotte